Exploration of Heat Strain during Light to Moderate Intensity Exercise throughout Pregnancy - Akbari, Pegah (Université d'Ottawa / University of Ottawa, 2018)
Regular physical activity is recommended in healthy pregnancies and has been shown to mitigate adverse pregnancy outcomes. Despite the benefits, many women do not adhere to the recommendations due to concerns of exercise-induced heat stress and the dangers it could pose to the developing fetus. While the majority of the concerns raised are not grounded in evidence, currently there are no studies that directly examine the isolated influence of pregnancy on metabolic heat production resulting from physical activity. Additionally, despite the prevalent use of psycho-physical tools in clinical settings, there is a scarcity of literature exploring the relationship between the physiological and perceptual measures of exercise-induced heat strain in the pregnant population. Therefore, objective one of this thesis was to quantify the heat production resulting from light to moderate physical activity (intensities recommended during pregnancy) throughout gestation. Secondly, in objective two, physiological and perceptual measures of thermal strain were compared and assessed throughout pregnancy. In evaluating the change in heat production resulting from exercise (objective one), 10 non-pregnant control (30±1 yrs; BMI=22.3±0.8 kg/m2) and 10 pregnant (32±1 yrs; pre-pregnancy BMI=22.8±0.8 kg/m2) women performed a seven stage submaximal walking test in a thermal controlled chamber (23ºC). Testing was performed during their 1st (T1, 12-16 wks), 2nd (T2, 24-28 wks) and 3rd (T3, 34-38 wks) trimester of pregnancy while metabolic heat production was measured through indirect calorimetry. To assess the changes in thermal and perceptual strain (objective two), 16 non-pregnant control (32±1 yrs; BMI=22.7±0.7 kg/m2), and 20 pregnant (32±1; pre-pregnancy BMI=23.2±0.6 kg/m2) women underwent a graded walking exercise protocol at T2 and T3. Over the course of this test, heart rate, tympanic temperature (Ttymp), skin temperature (Tskin), rate of perceived exertion (RPE, 20-point scale) and thermal sensation (9-point scale) were assessed. Findings from this thesis show that for the same given progressive exercise test, women in T1 experienced similar metabolic heat production to their non-pregnant counterparts. However, as pregnancy progressed, women exhibited on average, a 7-8% increase in heat production per trimester of pregnancy that can be accounted for by weight gain. Further, at baseline conditions, heart rate responses increased with pregnancy, while Ttymp remained unchanged and Tskin decreased. In response to exercise, the magnitude of change in heart rate, Ttymp and Tskin did not differ between gestational conditions. Finally, a strong correlation was identified between heart rate and RPE throughout pregnancy, while thermal sensation only directly correlated with Ttymp and not Tskin. Overall, the present findings suggest that while the same progressive exercise test results in greater levels of heat production as pregnancy progresses, this is not observed in physiological or perceptual measures of heat strain. Rather, findings of this thesis support the notion of improved thermoregulatory responses to account for the increase in metabolic heat production. Moreover, the present thesis provides support for the use of the RPE and thermal sensation scales as effective psycho-physical tools in the pregnant population under conditions of light to moderate exercise in normothermic conditions.
Keywords: Pregnancy; Exercise; Thermoregulation